1992
DOI: 10.1002/neu.480230914
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neuronal death in brain aging and alzheimer's disease: Role of endocrine‐mediated calcium dyshomeostasis

Abstract: This paper reviews evidence that brain aging and Alzheimer's disease (AD) are somehow closely related and that the hippocampus (CA1) is highly vulnerable to cell loss under both conditions. In addition, two current lines of evidence on the mechanisms of hippocampal cell loss with aging are considered, including studies of neuronal calcium dysregulation and studies of cumulative glucocorticoid (GC) neurotoxicity. Moreover, recent electrophysiological studies have shown that excess glucocorticoid activation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 108 publications
1
59
0
1
Order By: Relevance
“…These three alterations are not necessarily independent phenomena. A well documented example concerns the hypercorticism and increased GR affinity observed in the hippocampus of Fischer rats at old age, which correlates well with a GR-mediated increase of the Ca-influx through voltage-activated calcium channels (Kerr et al, 1992.…”
Section: Relevance For Pathological Conditionsmentioning
confidence: 87%
See 3 more Smart Citations
“…These three alterations are not necessarily independent phenomena. A well documented example concerns the hypercorticism and increased GR affinity observed in the hippocampus of Fischer rats at old age, which correlates well with a GR-mediated increase of the Ca-influx through voltage-activated calcium channels (Kerr et al, 1992.…”
Section: Relevance For Pathological Conditionsmentioning
confidence: 87%
“…Down regulation of GRs in brain and pituitary is commonly observed in aged Wistar and Fischer-344 rats, which show obvious signs of hypercorticism (Reul et al, 1988;Landfield et al, 1992; one report showed an impaired upregulation of the GRs (Eldridge et al. 1989).…”
Section: Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent hypothesis formulated by Cheng and Mattson proposes that the mechanisms by which trophic factors, such as NGF and bFGF, exert their protective effect on injured neurons could be through a stabilization in calcium homeostasis (Cheng and Mattson,199 1). The notion that disparate types of neuronal injuries are associated with calcium deregulation (Mattson, 1990;Strautman et al, 1990;Choi, 1992;Heizmann and Braun, 1992;Landfield et al, 1992) and the observation that their effects can be partially prevented by trophic factors (Fisher et al, 1987, 199 1;Cheng and Mattson, 1991) suggest that these different pathologies could share similar mechanisms of degeneration. Our findings of apoptosis in axotomized retinal ganglion cells raise the question as to whether a similar type of active, apoptotic death could occur in other neurodegenerative conditions.…”
Section: Discussionmentioning
confidence: 99%